(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B:s (NwOJNA I MIR(B: [(NrOMAN(B]; (NtOM (B2 /s (N~ASTX (B4s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NpRAWDA(B,s, 1987)
(Nw ^ETWERTYJ TOM WO[LEL ROMAN (B"(NwOJNA I MIR(B", (NTOM WTOROJ(B.s
rus
Keywords: (NrOMAN(B-(N\POPEQs